Pentingnya Karakter Komunikatif dalam Rumah Tangga - Suciati (IKOM UMY, 2015)
The essence of marrioge lies in the extent to the ability of each portner to integrate of the two different personolities. ln order to reolize the integration of personality depend on the intense communication between husband ond wife. Love and biological satisfaction may be moke fun at storting of the wedding. But this may not last long if each portner is not oble to integrate with each other and adapt to mointain friendship. On the other hand, when the integrotion of the personoLity embodied, it will make the feeling of hoppiness of the household. The marrioge often becomes routine life for the husbond and wife. They think that their portner should know whot the wishes. This is not true.